2015
DOI: 10.1016/j.jhep.2014.11.012
|View full text |Cite|
|
Sign up to set email alerts
|

The CLIF Consortium Acute Decompensation score (CLIF-C ADs) for prognosis of hospitalised cirrhotic patients without acute-on-chronic liver failure

Abstract: The new CLIF-C ADs is more accurate than other liver scores in predicting prognosis in hospitalised cirrhotic patients without ACLF. CLIF-C ADs therefore may be used to identify a high-risk cohort for intensive management and a low-risk group that may be discharged early.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
297
3
12

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 295 publications
(331 citation statements)
references
References 25 publications
12
297
3
12
Order By: Relevance
“…It was found that SBP alone accounts for 31%, almost one-third cases of acute deterioration in type I ACLF. A similar finding was reported by a Western study done by Jalan et al 6 Could hepatocellular carcinoma (HCC) be a cause of acute deterioration? The answer is HCC can lead to acute worsening.…”
Section: Cause Of Acute Deteriorationsupporting
confidence: 82%
“…It was found that SBP alone accounts for 31%, almost one-third cases of acute deterioration in type I ACLF. A similar finding was reported by a Western study done by Jalan et al 6 Could hepatocellular carcinoma (HCC) be a cause of acute deterioration? The answer is HCC can lead to acute worsening.…”
Section: Cause Of Acute Deteriorationsupporting
confidence: 82%
“…4C). Indeed, patients with higher chronic liver failure‐C (CLIF‐C) AD score, reflecting a high risk of ACLF,27 also had a higher deposition ratio (Fig. 4D).…”
Section: Resultsmentioning
confidence: 99%
“…This hypothesis gains considerable support by recent studies in patients with cirrhosis and SBP reporting that combined treatment with intravenous albumin and an antibiotic reduces the risk for renal dysfunction/failure and mortality in comparison to therapy with a single antibiotic [39]. Last but not least, clinical investigations, which clearly identified white blood cell count and C-reactive protein (CRP) as independent predictors of in-hospital survival, add great evidence to the prognosis-relevant role of SI [64,65]. More information on 'immune dysregulation' is given by Lange and Moreau [66] in this focus issue of Visceral Medicine.…”
Section: Immune Dysfunctionmentioning
confidence: 93%
“…In addition, a 'leaky gut' favoring translocation of bacteria towards the bloodstream along with a gradually impaired hepatic clearance capacity for bacterial antigens, such as lipopolysaccharide (LPS) or endotoxin, may induce activation of toll-like receptor (TLR) pathways, and, thus, further enhance SI that accelerates fibrogenesis and progression to liver cirrhosis [63]. This, in turn, boosts cytokine secretion along with an ongoing synthesis of reactive oxygen species (ROS), thereby forming a vicious circle in the development of intestinal inflammation and tissue hyperpermeability [64,65]. In this light, it is reasonable to assume that some beneficial effects of albumin administration in cirrhotic patients with SBP and/or type-1 HRS might be largely attributable to its anti-inflammatory and antioxidative stress properties [36].…”
Section: Immune Dysfunctionmentioning
confidence: 99%